Glass geochemistry and tephrostratigraphy of key tephra layers in and around Lake Van, Eastern Anatolian Volcanic Province (EAVP) - Rebecca J. Kearney; Jeremy Goff; Victoria Smith; Markus J. Schwab; Yavuz Özdemir; Özgür Karaoǧlu; Matthew Thirlwall; Dan N. Barfod; Oona Appelt; Christina Günter; Jan Fietzke; Nadine Pickarski; et al. (Quaternary Science Reviews, 2025)

Sediment-redox dynamics in an oligotrophic deep-water lake in Tierra del Fuego: insights from Fe isotopes - Luis Gabriel Ordoñez Rendón; Ina Neugebauer; Camille Thomas; Massimo Chiaradia; Nicolas Waldmann; Daniel Ariztegui (Journal of Paleolimnology, 2024)
For long time in the history of Earth, ferruginous conditions governed the oceans. With the rise of oxygen during the Proterozoic era and the subsequent evolution of living organisms, worldwide deposition of iron formations occurred. These sedimentary units reveal the transition into oxic oceans, passing by local and transitory euxinic conditions, especially in coastal shelves. Constraining the iron cycle and the biogeochemical processes occurring in present and past ferruginous basins helps answering some of the question regarding global oxygenation, the evolution of life and past climate changes. Therefore, Fe speciation and Fe isotopes in both Proterozoic and recent sedimentary records have been widely used to reconstruct past basin dynamics and redox conditions in the sediment–water interface. However, sedimentation and early diagenesis can alter paleoredox proxies and their primary climate signals. In this work, we disentangled alteration processes occurring at the redox front below the sediment–water interface of a ventilated deep-water lake (Lago Fagnano, Argentina/Chile). A sequential extraction protocol was applied to characterize two reactive Fe pools: Fe oxyhydroxides and reduced iron. Subsequently, Fe isotopes were constrained to determine the main processes mobilizing Fe. At the redox front, ferric minerals reach a δ 56 Fe value of − 1.3‰ resulting from oxidation of dissolved Fe likely following a Rayleigh distillation effect. Dissolved Fe is produced right below via Fe reduction, as shown by the low ferric Fe content. Our observations delineate a redox cycle and a redox horizon undergoing constant upward migration, initiated by regular sedimentation. However, during events of increased rapid sedimentation (e.g., seismites) this dynamic cycle is interrupted inducing full or partial preservation of the Fe-rich redox front. In such case, oxidation of dissolved Fe is interrupted and can be recycled in ferrous minerals, such as Fe monosulfides and amorphous phases with δ 56 Fe values down to − 1.7 ‰. These findings have significant implications for the recording of biogeochemical cycles in the geological past, the use of Fe isotopes in freshwater-lake sediments for paleoclimate studies, and the progress of our knowledge regarding the geochemistry of past oceans.

Boron geochemistry reveals the evolution of Dead Sea brines - Hana Jurikova; Simon J. Ring; Michael J. Henehan; Ina Neugebauer; Birgit Schröder; Daniela Müller; Markus J. Schwab; Rik Tjallingii; Achim Brauer; Cécile Blanchet (Earth and Planetary Science Letters, 2023)

Reconstruction of Dead Sea lake level and mass balance back to 237 ka BP using halite fluid inclusions - Emmanuel Guillerm; Véronique Gardien; Nicolas D. Waldmann; Niels S. Brall; Daniel Ariztegui; Markus J. Schwab; Ina Neugebauer; Adeline Lach; Frédéric Caupin (Quaternary Science Reviews, 2023)